A novel dosing approach for rituximab in glomerular diseases based on a population pharmacokinetic analysis - Hartinger, Jan Miroslav; Šíma, Martin; Hrušková, Zdenka; Pilková, Alena; Krátký, Vojtěch; Ryšavá, Romana; Jančová, Eva; Bobek, Daniel; Douša, Jiří; Francová, Ivana; Tesař, Vladimír; Slanař, Ondřej (Biomedicine & pharmacotherapy, 2024)
OBJECTIVES: Rituximab is being increasingly prescribed for the treatment of autoimmune glomerular diseases. While it is highly effective for some diseases, the response is less predictable for others, which may be due to differing requirements in terms of the dosing according to the disease type and variations concerning exposure to the drug. METHODS: We compiled novel rituximab dosing schedules according to pharmacokinetic analysis of data gathered from rituximab treated patients in a tertiary referral nephrology centre between May 2020 and June 2023. The population-pharmacokinetic analysis was based on the rituximab dosing, the patients' characteristics, rituximab levels and anti-rituximab antibodies. RESULTS: The analysis, which was based on data from 185 patients, clearly highlighted differing rituximab dosing requirements for patients with ANCA associated vasculitis and minimal change disease compared to those with membranous nephropathy, focal-segmental glomerulosclerosis and lupus nephritis. This corresponded to the good treatment response of the first two diseases and the unreliable efficacy for the others. The model predicts the rituximab pharmacokinetics with high degree of accuracy when body weight, proteinuria, type of glomerulonephritis, treatment length and anti-rituximab antibodies formation are used as covariates. We proposed a dosing schedule with shortened dosing intervals for difficult-to-treat diagnoses with high proteinuria. CONCLUSION: In order to ensure reliable and comparable exposure of rituximab with respect to the full range of glomerular diseases, the dosing schedule should be adjusted for membranous nephropathy, focal-segmental glomerulosclerosis and lupus nephritis. This is largely, but not solely, due to the enhanced level of unselective proteinuria in these diseases.
Keywords: rozvrh dávkování léků; Drug Administration Schedule; mužské pohlaví; Male; senioři; výsledek terapie; Female; Humans; rituximab; lidé; membranózní glomerulonefritida; Glomerulonephritis, Membranous; Middle Aged; ženské pohlaví; lidé středního věku; vztah mezi dávkou a účinkem léčiva; Rituximab; Models, Biological; Young Adult; biologické modely; Dose-Response Relationship, Drug; Treatment Outcome; Glomerulonephritis; mladý dospělý; dospělí; Adult; glomerulonefritida; Aged